Implementation of Project Based Learning in Mathematics Capita Selecta for Elementary School - Hanifah, Hanifah; Utari, Tria (FKIP Universitas Lampung, 2022)
Mathematics Capita Selecta For Elementary School is a course that aims to produce students who are able to find solutions to problems that occur in learning mathematics in elementary schools. To achieve this, implementing the Project Based Learning (PjBL) model is the right choice, because PjBL is a student-centered learning model. This study aims to find out impact of the implementation of the Project Based Learning (PjBL) model which is applied to the Mathematics Capita Selecta for Elementary School course. The subjects in this study were 31 students of the Mathematics Education Study Program University of Bengkulu 2021/2022 who took the courses. Data collection method used is open-ended tests and surveys using questionnaire response. Research results show that students’ learning outcome is at the value of 75 obtained from the t test using SPSS software, where obtained P-Value>0,05. Besides that, results research also shows that response student to learning is very good with percentage of 64.52% and good with percentage of 35.48%.Keywords: project based learning, mathematics capita selecta , elementary schoolDOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1738-1750